BEBERAPA GENERALISASI TEOREMA TITIK TETAP CARISTI UNTUK JARAK-ω - Ahmad Khairul Umam; Pukky Tetralian Bantining Ngastiti; Ahmad Isro'il (MathVisioN, 2024)
Caristi’s fixed point theorem is generalization of Banach’s fixed point. Banach’s fixed point theorem guarantee existence and uniqueness fixed point in complete space and contractive function. Caristi’s fixed point uses function f:X→X and lower semicontinuous function ψ:X→[0,∞). In this paper, we discuss some generalization of Caristi’s fixed point theorem. We also use ω-distance as distance function. We discuss function T:X→2^X where 2^X are collection of all nonempty subsets of X. And then we use function c:[0,∞)→(0,∞) that is nondecreasing function.